Experiential Metafunction Analysis on A Thousand Years Song by Christina Perri - Lihardo Manik; Selviana Napitupulu (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study analyzes the experiential metafunction in Christina Perri’s song A Thousand Years using Halliday’s Systemic Functional Linguistics, with emphasis on the transitivity system. A qualitative descriptive approach was employed by segmenting the lyrics into clauses and identifying process types, participants, and circumstances. The analysis reveals six process types, with mental processes dominating (39%), followed by relational (28%) and material processes (22%), while verbal, behavioral, and existential processes appear minimally. The findings indicate that the song constructs meaning primarily through emotional expression, psychological states, and identity rather than physical action. Linguistically, the transitivity patterns represent themes of eternal love, fear, hope, and emotional endurance. This study demonstrates that song lyrics serve as meaningful linguistic data for exploring experiential meaning and may be effectively applied in language learning contexts, particularly in the teaching of functional grammar and discourse analysis.